2012
DOI: 10.1094/cchem-08-11-0096
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Puroindoline b Gene Involvement in the Milling Behavior of Hard‐Type Common Wheats

Abstract: Differences in milling behavior among hard‐type common wheat (Triticum aestivum) cultivars are well known to millers. Among them, the French cultivar Soissons, which contains the Pinb‐D1d allelic form of the puroindoline b gene, is particularly distinguished for its high milling value. Near‐isogenic lines (NILs) differing by the allelic forms of the puroindoline b gene, Pinb‐D1d or Pinb‐D1b (one of the most frequent alleles found in the European wheat population), were constructed. Grain characteristics obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In one example, Tsilo et al identified a QTL linked to chr. 5DS using a bi-parental population in which the two parents both had an identical Pin genotype and the hard-kernel phenotype, indicating that another gene, likely closely linked to the Ha locus, may be responsible for the phenotypic variation [89]. Recently, a transgenic study of GSP on the Ha locus showed that regulation of GSP can have a small effect on grain hardness, coinciding with the minor QTL detected on chr.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In one example, Tsilo et al identified a QTL linked to chr. 5DS using a bi-parental population in which the two parents both had an identical Pin genotype and the hard-kernel phenotype, indicating that another gene, likely closely linked to the Ha locus, may be responsible for the phenotypic variation [89]. Recently, a transgenic study of GSP on the Ha locus showed that regulation of GSP can have a small effect on grain hardness, coinciding with the minor QTL detected on chr.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Numerous studies have been focused on mining allelic variations and the genotype-phenotype association of Pin, resulting in the identification of 26 alleles of Pina, 33 alleles of Pinb and a few double null alleles [21,22,[77][78][79][80][81][82][83][84][85][86][87]. Manipulation of the expression or genotypes of Pin not only modifies kernel hardness and milling properties in common and durum wheat lines [62][63][64]67,[88][89][90][91][92], but also changes some parameters of the end-use quality and storage protein interaction [29,[93][94][95]. Owing to its importance, research regarding Pin has been comprehensively reviewed by Bhave et al [21,22] in aspects of its genetics, polymorphism identification and studies about its biological functions.…”
Section: Pins Are the Major Causal Genes For Wheat Kernel Hardnessmentioning
confidence: 99%
“…Grain hardness changes conditioned by puroindolines are positively correlated with flour yield and negatively correlated with break flour yield (Campbell et al 2001;Martin et al 2001Martin et al , 2007Hogg et al 2005;Reynolds et al 2010aReynolds et al , 2010b. Even small changes in grain hardness such as the 5-10 units that separate seeds carrying different Pin alleles common in hard wheats are enough to significantly modify milling and baking properties (Martin et al 2001;Ma et al 2009;Takata et al 2010;Lasme et al 2012). It is therefore to be expected that generating novel puroindoline alleles with unique hardness levels would expand the range in milling traits, some of which should give improved performance over common Pin alleles.…”
mentioning
confidence: 99%
“…In wheat cultivars, this texture trait is determined by the Puroindoline a ( Pina ) and Puroindoline b ( Pinb ) gene alleles at the Hardness locus ( Ha ) [ 5 ]. Although the genetic determinants that distinguish soft and hard wheat are known [ 30 , 31 ], what is known in less detail is the relationship between the genes and the biochemical and biomechanical basis for the grain hardness differences. Soft and hard wheat starchy endosperms differ in their puroindoline a (PINA) and b (PINB) protein contents, but how this translates into defined biomechanical differences that underpin the distinct milling and flour properties is still unclear.…”
Section: Introductionmentioning
confidence: 99%